2001
DOI: 10.1021/tx000251l
|View full text |Cite
|
Sign up to set email alerts
|

Methylated Trivalent Arsenic Species Are Genotoxic

Abstract: The reactivities of methyloxoarsine (MAs(III)) and iododimethylarsine (DMAs(III)), two methylated trivalent arsenicals, toward supercoiled phiX174 RFI DNA were assessed using a DNA nicking assay. The induction of DNA damage by these compounds in vitro in human peripheral lymphocytes was assessed using a single-cell gel (SCG, "comet") assay. Both methylated trivalent arsenicals were able to nick and/or completely degrade phiX174 DNA in vitro in 2 h incubations at 37 degrees C (pH 7.4) depending on concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
296
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(316 citation statements)
references
References 46 publications
17
296
0
3
Order By: Relevance
“…Family members who resided in Chiu Chiu had a high prevalence of arsenic-induced skin lesions. It had been thought that methylation reduced the toxicity of arsenic (12), but recent laboratory evidence suggests that methylated trivalent MMA may be more toxic than the inorganic forms (14,26). The low values of InAs/metAs found in family A could indicate that the biotransformation of arsenic through methylation may be associated with increased health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Family members who resided in Chiu Chiu had a high prevalence of arsenic-induced skin lesions. It had been thought that methylation reduced the toxicity of arsenic (12), but recent laboratory evidence suggests that methylated trivalent MMA may be more toxic than the inorganic forms (14,26). The low values of InAs/metAs found in family A could indicate that the biotransformation of arsenic through methylation may be associated with increased health effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, this notion was based on an earlier, incomplete understanding that did not take into account the intermediate trivalent metabolites, MMA III and DMA III . Recent studies of human cytotoxicity of As III , MMA III , and DMA III (9); acute toxicity in hamsters (10); enzyme inhibition (10 -12); and potent ability to cause DNA damage (13) have shown that MMA III and DMA III are at least as toxic as, if not more so than, inorganic arsenic species. These new findings challenge the conventional wisdom of arsenic toxicity with regard to biomethylation, which may actually be an activation process.…”
Section: Inorganic Arsenicmentioning
confidence: 99%
“…Some evidence shows that the trivalent arsenic species cause oxidative damage to DNA (13,40). Electron spin resonance with spin trapping has detected free radicals produced in cells incubated with As III (41).…”
Section: Understanding Arsenic's Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation is considered as the most important natural transformation path that converts inorganic arsenic into organic arsenic species of lower toxicity such as monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA) [1,2]. Recent studies revealed that methylation also leads to the formation of highly toxic trivalent intermediates that are not stable under nonphysiological conditions [3]. Otherwise, several phenylarsenic compounds, namely, 4-hydroxy-3-nitrobenzenearsonic acid (roxarsone), phenylarsonic acid (PAA), p-aminophenylarsonic acid (p-APAA) and o-aminophenylarsonic acid (o-APAA), are of industrial origin and are commonly used as animal-feed additives [4].…”
Section: Introductionmentioning
confidence: 99%